Determinantes do nível de caixa das empresas: análise de amostra de países da América Latina - Dylewski, Carolina (2010)
We examine, using panel data modeling techniques, the determinants of corporate liquidity in a sample of publicly traded firms in Brazil, Argentina, Chile, Mexico and Peru in the 1995-2009 period. In this paper, the ratio utilized in the models is denominated liquid assets (or simply cash), which includes the available cash and the investment in short term securities, divided by the firm’s total assets. It is possible to identify an increasing trend in the firms’ liquid assets ratio in the period analyzed for the majority of the countries. We find evidence that firms with stronger growth opportunities, larger total assets position, higher dividends payment and higher profitability, accumulate more cash. Also, firms with higher capital expenditures, higher cash flow generation and cash flow volatility, stronger leverage position and higher working capital level accumulate less cash. We identify similarities in the determinants of corporate liquidity with the empirical studies of firms in developed countries, as well as differences due to specific characteristics in emergent economies such as high internal interest rates, different access levels to international credit market and to development agencies credit lines, equity kicking, among others. We find evidence in tests applied for Brazil’s largest firms sample the presence of cash target levels through first order auto regressive model (AR1). Variables utilized in tests in recent papers with firms in developed economies such as acquisitions, recent IPO activities and corporate governance level are also tested for Brazil’s firms sample.